Analisis Kebutuhan Kegiatan Pelatihan di Desa Pao Kabupaten Gowa Provinsi Sulawesi Selatan - Hasbi, Andi; Ab., Ahmad; Poke, Andi Alif Rahmatullah; Yusran, Muhammad; Agus (Jurnal Abdimas Pariwisata, 2024)
Needs Analysis of Training Activities in Pao Village, Gowa Regency, South Sulawesi Province The purpose of this community service activity is to analyze the training needs needed for the community as business actors in Pao Tourism Village.  This activity is expected to help the community in the tourism awareness working group in adding skills, especially in the field of food and beverage services related to environmentally friendly food packaging. Other training related to improving the quality of human resources that sustain tourist villages as locomotives of economic growth based on community participation. The method used in this community service activity is to analyze training needs through focus group discussion (FGD) activities. From the results of the FGDs, the required training was identified, including training for tourism business actors such as culinary production houses, training in making "bedda lotong", training in homestay management, especially on homestay services, room preparation and financial management, and training on food and beverage service standards both in terms of food and beverage production and in the context of packaging.